(untitled) (Italiano LinguaDue, 2021)
Si dimostrerà, attraverso il commento di fenomeni linguistici e scene operistiche esemplari, l’utilità didattica dell’opera lirica, non soltanto dai punti di vista linguistico, transdisciplinare, socioculturale, storico-artistico, ma anche semiotico e multimodale. Soprattutto le variabilità diacronica e diafasica si prestano a essere esemplificate dai testi operistici, data la ricca presenza di arcaismi, aulicismi e poetismi, ma anche di espressioni idiomatiche. Tra i fenomeni analizzati: l’imperativo, il gerundio, i verbi transitivi e intransitivi, l’ordine dei costituenti, la formazione delle parole e il che polivalente. All’opera! Proposals for teaching Italian (L1 and L2) through opera Through the commentary of linguistic phenomena and exemplary opera scenes, we will demonstrate the didactic usefulness of opera, not only from a linguistic, transdisciplinary, sociocultural, historical and artistic point of view, but also from a semiotic and multimodal one. Above all, the diachronic and diaphasic variability lends itself to be exemplified by opera texts, given the rich presence of archaisms, aulicisms and poeticisms, but also of idiomatic expressions. Among the phenomena analyzed: the imperative, the gerund, transitive and intransitive verbs, constituent order, word formation, and polyvalent “che”.